Genomic data as the hitchhiker's guide to cattle adaptation: tracking the milestones of past selection in the bovine genome - Utsunomiya, Yuri T. [UNESP]; Pérez O'Brien, Ana M.; Sonstegard, Tad S.; Sölkner, Johann; Garcia, José F. [UNESP] (Frontiers In Genetics, 2015)
The bovine species have witnessed and played a major role in the drastic socio-economical changes that shaped our culture over the last 10,000 years. During this journey, cattle hitchhiked on human development and colonized the world, facing strong selective pressures such as dramatic environmental changes and disease challenge. Consequently, hundreds of specialized cattle breeds emerged and spread around the globe, making up a rich spectrum of genomic resources. Their DNA still carry the scars left from adapting to this wide range of conditions, and we are now empowered with data and analytical tools to track the milestones of past selection in their genomes. In this review paper, we provide a summary of the reconstructed demographic events that shaped cattle diversity, offer a critical synthesis of popular methodologies applied to the search for signatures of selection (SS) in genomic data, and give examples of recent SS studies in cattle. Then, we outline the potential and challenges of the application of SS analysis in cattle, and discuss the future directions in this field.
Keywords: Bos indicus; Bos taurus; Adaptation; Positive selection; Single nucleotide polymorphism